2009
DOI: 10.1590/s0006-87052009000100025
|View full text |Cite
|
Sign up to set email alerts
|

Uso de hipoclorito de sódio para acelerar a emergência das plântulas e o desenvolvimento das mudas de cafeeiro

Abstract: RESUMOO objetivo do presente trabalho foi avaliar o efeito das concentrações de hipoclorito de sódio em solução aquosa de pré-embebição das sementes sobre a porcentagem e velocidade de emergência das plântulas de cafeeiro, bem como avaliar o desenvolvimento das mudas. Cinco ensaios foram realizados, sendo um para cada grau de umidade das sementes (13%, 18, 23%, 28% e 33% base úmida). Cada ensaio constituiu-se de cinco tratamentos, formados por sementes pré-embebidas em três concentrações de solução aquosa cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 4 publications
1
5
0
5
Order By: Relevance
“…The seeds of this species have a high degree of susceptibility to injury caused by rapid soaking through immersion in distilled water. For coffee beans (Coffea arabica L.), Sofiatti et al (2009) found that seed soaked in sodium hypochlorite at concentrations of 4, 5, and 6% caused a reduction in seed germination and vigor.…”
Section: Resultsmentioning
confidence: 99%
“…The seeds of this species have a high degree of susceptibility to injury caused by rapid soaking through immersion in distilled water. For coffee beans (Coffea arabica L.), Sofiatti et al (2009) found that seed soaked in sodium hypochlorite at concentrations of 4, 5, and 6% caused a reduction in seed germination and vigor.…”
Section: Resultsmentioning
confidence: 99%
“…De acordo com Sofiatti et al (2009) Na presente pesquisa, as sementes de café ficaram expostas por 6 horas à solução, o que pode ter provocado uma maior absorção de substâncias prejudiciais ao embrião, efeito constatado nos embriões que apresentavam maior descoloração na radícula.…”
Section: Resultsunclassified
“…O procedimento de remoção de pergaminho na avaliação da qualidade é trabalhoso e demanda muita mão de obra. Uma alternativa recentemente recomendada é a utilização do hipoclorito de sódio (NaClO), técnica investigada por Meirelles et al (2007), Lima (2008) e Sofiatti et al (2009) com resultados satisfatórios. O uso da solução de hipoclorito de sódio, na concentração de 5,0% durante 6 horas, foi eficiente na degradação do pergaminho, observado por Meirelles et al (2007).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…An alternative proposed by Meireles et al (2007) to facilitate removal of the endocarp is utilization of a sodium hypochlorite solution at a concentration of 5.0% for 6 hours. Nevertheless, Sofiatti et al (2009) observed a negative effect of hypochlorite for seeds with a moisture content below 23% in germination test results. In addition, Rubim et al, (2010) observed that "conilon" coffee seeds exhibited low germination when submitted to sodium hypochlorite aqueous solution at a concentration of 4% for three hours, in addition to complete degradation of the parchment not being observed.…”
Section: Introductionmentioning
confidence: 91%